A prediction of borehole stability while drilling preliminary prospecting wells based on seismic impedance - Chao WU; Jianhua LIU; Dongqing ZHANG; Xiaofeng CHEN; Weijie ZHAO (Petroleum Exploration and Development, 2015)
When the conventional method of predicting borehole stability is applied to the preliminary prospecting wells, the precision of prediction is often affected severely by the lack of data, limit of applying conditions, error of calculated parameters and complexity of operating courses. This paper presents a method of predicting borehole stability while drilling preliminary prospecting wells and establishes a nonlinear model including wave impedance and borehole stability mechanical parameters by investigating the quantitative relationships between wave impedance and pore pressure, in-situ stress as well as rock strength. Based on the nonlinear model, neural network algorithm is used to identify the relationship between the wave impedance and the three formation pressures (pore pressure, fracture pressure and collapse pressure). Through the establishment of the model by layered neural network and the timely analysis of logging data, the wellbore stability before the bit can be predicted while drilling by using the data of seismic wave impedance. Field application in preliminary prospecting wells shows that the new method has higher adaptability, faster calculation speed, and simpler operational procedure than conventional methods, and its prediction accuracy can meet the requirement of engineering. Key words: preliminary prospecting well, borehole stability, prediction while drilling, wave impedance, neural network